Migrant Semipalmated Sandpipers (Calidris pusilla) Have Over Four Decades Steadily Shifted Towards Safer Stopover Locations - Hope, David D.; Lank, David B.; Smith, Paul A.; Paquet, Julie; Ydenberg, Ronald C. (Frontiers in Ecology and Evolution, 2020)
Peregrine falcons (Falco peregrinus) have undergone a steady hemisphere-wide recovery since the ban on DDT in 1973, resulting in an ongoing increase in the level of danger posed for migrant birds, such as Arctic-breeding sandpipers. We anticipate that in response migrant semipalmated sandpipers (Calidris pusilla) have adjusted migratory behaviour, including a shift in stopover site usage towards locations offering greater safety from falcon predation. We assessed semipalmated sandpiper stopover usage within the Atlantic Canada Shorebird Survey dataset. Based on 3,030 surveys (totalling ̃32M birds) made during southward migration, 1974 - 2017, at 198 stopover locations, we assessed the spatial distribution of site usage in each year (with a ‘priority matching distribution’ index, PMD) in relation to the size (intertidal area) and safety (proportion of a site’s intertidal area further than 150m of the shoreline) of each location. The PMD index value is > 1 when usage is concentrated at dangerous locations, 1.0 when usage matches location size, and < 1 when usage is concentrated at safer locations. A large majority of migrants were found at the safest sites in all years, however our analysis of the PMD demonstrated that the fraction using safer sites increased over time. In 1974, 80% of birds were found at the safest 20% of the sites, while in 2017, this had increased to 97%. A sensitivity analysis shows that the shift was made specifically towards safer (and not just larger) sites. The shift as measured by a PMD index decline cannot be accounted for by possible biases inherent in the data set. We conclude that the data support the prediction that increasing predator danger has induced a shift by southbound migrant semipalmated sandpipers to safer sites.